MOTHERHOOD IN PRISON: RIGHTS AND CHALLENGES OF PREGNANT INMATES IN BRAZIL. (REMUNOM, 2025)
Maternity in prison is a topic that raises profound reflections on human rights, the prison system, and public policies in Brazil. This literature review article aims to analyze the main challenges faced by pregnant women in situations of deprivation of liberty, as well as the rights guaranteed by national and international legislation. The research shows that pregnant inmates often experience violations of fundamental rights, such as inadequate access to health services, lack of qualified prenatal care, unsanitary conditions of incarceration, and early separation from the baby after birth. Despite the existence of regulations such as Law No. 13,769/2018, which allows the replacement of preventive detention with house arrest for pregnant women and mothers of young children, the application of these measures still faces resistance and inequality. The review also points to the lack of effective public policies and the social invisibility of these women, who end up suffering a double penalty: for the offense committed and for motherhood experienced under surveillance. It is concluded that it is essential to broaden the public debate, raise awareness among agents of the penal system and effectively implement measures that guarantee the dignity, health and well-being of mothers and children in the prison context.